Effect of hyperglycemic condition on observed surface area to volume ratio of human cancerous cells - Naseri, Mohammad Hassan; Hesami Tackallou, Saeed; Rezaei Tavirani, Mostafa (Archives of Advances in Biosciences, 2012)
The human blood basal glucose level is a completely controlled range. Information on the relationship between culture glucose concentration and changes in the cell's surface area, volume and surface area to volume (S/V) ratio are lacking. Cancerous epithelial-like cell lines SW480, SW742 and T-47D were cultured in mediums nourished with 4.7 mM per liter of glucose as the control group and three other groups with glucose concentrations of 9.4, 14.1 and 18.8 mM at 37 °C for 48hr. Digital images of cells were analyzed using the ImageJ software. Observed changes in surface area, volume, and surface area to volume (S/V) ratio were significantly (P<0.05) different between the control group and the X4 group (18.8 mM glucose) in the three cell lines tested. Cultured cells responded delicately but sharply to glucose elevation. The goal of this research is to show the dictating of changes via pathologic conditions in cellular levels that could be a good answer to changing the body metabolic parameters. Besides the S/V ratio could be studied as a variant parameter in other metabolic challenges.